AN INVESTIGATION OF THE COMPASSION LEVELS OF HEALTH PROFESSIONALS CANDIDATES - Fadime CINAR*, Hasim CAPAR (Innovative Journal of Medical and Health Sciences, 2019)
The aim of this study is to determine the factors affecting the level of compassion and the compassion levels of professionals candidates. The population of this study consisted of 1382 students from Nutrition and Dietetics, Child Development, Physiotherapy and Rehabilitation, Nursing and Health Management. “Demographic Information Form” which was developed by researchers in the literature and Compassion Scale developed by Pommier (2011) and also adapted to Turkish by Akdeniz and Deniz (2016) which able to measure compassion towards others was used as a data collection tool. In the study, 34.7% of the professional health candidates were in the Nutrition and Dietetics Department, 33% were 20 years old and 78.7% were women. The mean score of the Compassion Scale of all students was 4.22 ± 0.24. There was a statistically significant difference (p <.05) between the scores of the first grade to the last grade. A statistically significant difference was found in terms of indifference, seperation, mindfulness, disengagement sub-dimensions and general compassion scale scores. It was determined that compassion levels of health professionals candidates differed in terms of gender, class and income status. In light of the findings obtained, it can be explained in the lessons as a subject of compassion for the awareness of the emotions that will affect the feelings of compassion of the students of the health sciences faculty who will be health professionals of the future. Keywords: Compassion; Health Professionals; Compassionate Health Care